2006
DOI: 10.1128/iai.00440-06
|View full text |Cite
|
Sign up to set email alerts
|

IpaD Localizes to the Tip of the Type III Secretion System Needle of Shigella flexneri

Abstract: Shigella flexneri, the causative agent of shigellosis, is a gram-negative bacterial pathogen that initiates infection by invading cells within the colonic epithelium. Contact with host cell surfaces induces a rapid burst of protein secretion via the Shigella type III secretion system (TTSS). The first proteins secreted are IpaD, IpaB, and IpaC, with IpaB and IpaC being inserted into the host cell membrane to form a pore for translocating late effectors into the target cell cytoplasm. The resulting pathogen-hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
248
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 163 publications
(262 citation statements)
references
References 45 publications
13
248
0
1
Order By: Relevance
“…In this case, the alteration in cross-linking pattern could correspond to states in which CdsF is interacting with different proteins. For example, CdsF likely interacts with translocator proteins embedded in the inclusion membrane in the context of a native infection, whereas in EBs it could interact with capping proteins similar to those described for Shigella or Yersinia needles (13,41). Regardless of the mechanism, it is therefore probable that the different dominant bands seen here in the cross-linking ladders during active T3S (RBs) and inactive T3S (EBs) represent an alteration in the functional state CdsF.…”
Section: Vol 190 2008mentioning
confidence: 83%
“…In this case, the alteration in cross-linking pattern could correspond to states in which CdsF is interacting with different proteins. For example, CdsF likely interacts with translocator proteins embedded in the inclusion membrane in the context of a native infection, whereas in EBs it could interact with capping proteins similar to those described for Shigella or Yersinia needles (13,41). Regardless of the mechanism, it is therefore probable that the different dominant bands seen here in the cross-linking ladders during active T3S (RBs) and inactive T3S (EBs) represent an alteration in the functional state CdsF.…”
Section: Vol 190 2008mentioning
confidence: 83%
“…The needle is ϳ50 nm in length, has an outer diameter of 7.0 nm, and possesses an inner channel that is ϳ2.0 -3.0 nm in diameter (10,11). We recently demonstrated that invasion plasmid antigen D (IpaD) localizes to the tip of the TTSA needle (12), where it controls secretion of the translocator proteins IpaB and IpaC and directs their insertion into host cell membranes (13). From its position at the TTSA needle tip, IpaD is responsible for recruiting and stably maintaining IpaB to this site in the presence of bile salts (14).…”
Section: From the Department Of Molecular Biosciences University Of mentioning
confidence: 99%
“…From its position at the TTSA needle tip, IpaD is responsible for recruiting and stably maintaining IpaB to this site in the presence of bile salts (14). This is an essential step for Shigella invasiveness, and the interactions between IpaD and MxiH that are responsible for tip complex stabilization are thus critical for Shigella pathogenesis (12,14).…”
Section: From the Department Of Molecular Biosciences University Of mentioning
confidence: 99%
“…Purified IpaB and IpaC integrate into host-cell plasma membranes (De Geyter et al, 1997, and IpaB induces liposome fusions in vitro (Hume et al, 2003). IpaD localizes to the tip of the needle prior to secretion and likely serves as a scaffold for the assembly of the hydrophobic IpaBC translocon (Espina et al, 2006). IpaB and IpaC also have effector functions: while microinjected IpaC triggers actin polymerization and filopodia formation in epithelial cells (Tran Van Nhieu et al, 1999), microinjected IpaB triggers cell death in macrophages (Chen et al, 1996).…”
Section: Introductionmentioning
confidence: 99%